Radiographic risk factors for degenerative lumbar spondylolisthesis: A comparison with healthy control subjects - Wang, Zheng; Tian, Yonghao; Li, Chao; Li, Donglai; Ibrahim, Yakubu; Yuan, Suomao; Wang, Xia; Tang, Juan; Zhang, Shijun; Wang, Lianlei; Liu, Xinyu (Frontiers in Surgery, 2022)
Objective: To evaluate the radiologic parameters of degenerative lumbar spondylolisthesis (DLS) and determine the radiographic risk factors for DLS by making comparisons with healthy control subjects. Methods: Seventy-five patients with L4/5 DLS (Meyerding grade I) and 53 healthy control subjects were analyzed. The L1-S1 disc height (DH), disc height index (DHI), L4/5 facet joint angle (FJA), paravertebral muscle cross-sectional area (CSA), and related CSA (RCSA) were measured in both groups. The initial L4/5 DH (iDH) and DHI (iDHI) before the onset of DLS were estimated based on the L3/4 DHI of the DLS group and DHI of the control group. The sagittal parameters of DLS were also included in this study. Results: The DH and DHI of L4/5 were lower in the DLS group than in the control group (P<0.05), but the DH and DHI of the L1-L4 segment was much higher than in the control group (P<0.05). The iDHI and FJA of the DLS group were significantly higher than those of the control group (P<0.05). The CSA and RCSA of the paravertebral muscles were smaller in the DLS group than in the control group (P<0.05). Binary logistic regression analysis showed that iDHI, FJA, and RCSA of the total paraspinal muscle were risk factors for DLS. The cutoff values for iDHI, FJA, and RCSA were 0.504, 56.968°, and 1.991 respectively. The iDHI was associated with lumbar lordosis, while L4/5 DHI was associated with the RCSA of the multifidus muscle and psoas major muscle (P<0.05). Conclusion: A large initial lumbar disc height, large FJA, and paravertebral muscle atrophy may be risk factors for DLS.